Grãos inteiros de milho, aveia branca ou arroz com casca na terminação de bovinos confinados desempenho e comportamento ingestivo - Argenta, Flânia Mônego (2015)
Aimed to evaluate the performance and ingestive behavior of cattle finished in feedlot with whole grains based on corn, white oat or rice with hulls. Forty- five animals from double-cross cross breeding involving Charolais and Nellore races belonging to the Beef Cattle Department, with initial average weight and age of 310 kg and 20 months for the steers and 350 kg and 32 months for the heifers were used. The animals were randomly distributed in the treatments, blocked according the category (8 steers and 7 heifers), totaling 15 animals per treatment placed in individual stalls. The diets were calculated in order to be isonitrogenous, being the treatments composed by: Rice (85% of rice + 15% core protein); Oat (85% oat + 15% core protein) and Corn (85% corn + core protein), besides limestone and urea in order to balance the demands of calcium and nitrogen, respectively. The daily dry matter and crude protein intake did not differ among the different tested grains. The intake of ether extract, neutral detergent fiber and hemicellulose were superior for the animals that consumed oat grain, presenting values of 0.09; 0.65 and 0.34 % LW, respectively. Regarding the cellulose intake, the treatments oat (0.22% LW) and rice (0.18% LW) were superior to the corn treatment (0.06% LW). Regarding the intake of total digestible nutrients, non- fiber carbohydrates and total carbohydrates, there were no significant difference. For the variable final weight the animals of corn and oat treatment were superior to the rice treatment. Regarding the daily average gain, the animals fed with corn were superior to the oat treatment, being this one superior to the animals fed with rice, presenting values of 1.30; 1.07 and 0.71 kg, respectively. The animals of rice treatment obtained worse feed conversion compared to the corn and oat treatment that were better and similar, being 11.15; 6.07 and 7.99 kg LW/ kg DM, respectively. The animals that received the diet based on corn remained more time in idle (19.87 hours) compared to the animals fed with rice (18.58 hours), and these ones remained more time in idle in relation to the ones fed with oat (15.64 hours). Regarding the rumination time, the animals that consumed the diet based on oat, spent more time ruminating (6.38 hours) than the animals of rice treatment (3.23 hours) and these ones spent more time ruminating than the animals of the corn based diet (1.90 hours). The animals fed with corn remained less time eating and presented higher number of daily meals when compared to the other treatments. The use of diets with whole grain on feedlot cattle finishing is a viable alternative, wherein corn or oat presented better animal response in relation to rice with hulls. In this type of diet, the NDF level influence the time spent by the animals with rumination and idle, however, for the feeding time, there is no variation.